2022
DOI: 10.3390/healthcare11010101
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Technologies and Quadriplegia: A Map Point on the Development and Spread of the Tongue Barbell Piercing

Abstract: The barbell piercing can be used as an assistive device that allows people with severe disabilities, such as tetraplegia, to control their environments using the movement of the tongue. The human tongue can move rapidly and accurately, such that the tip can touch every tooth. Lingual control systems allow people with disabilities to take advantage of their residual skills for easier communication and to improve the control of mobility and the surrounding environment. The aim of this study was to conduct a narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…There is an increasing need for studies focused on AI in clinical These developments can streamline the health domain processes and change the role and workflow of the professionals already involved in the decision-making process, such as radiologists, pathologists, cytologists, histologists, and dermatologists. However, other professional figures will also be able to make use of AI in the workflow, such as the medical radiology technician, the biological laboratory technician, and even the tattoo artists, who will be able to interact with other professional figures in diagnostics to monitor any problems [20] of this widespread practice [21].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing need for studies focused on AI in clinical These developments can streamline the health domain processes and change the role and workflow of the professionals already involved in the decision-making process, such as radiologists, pathologists, cytologists, histologists, and dermatologists. However, other professional figures will also be able to make use of AI in the workflow, such as the medical radiology technician, the biological laboratory technician, and even the tattoo artists, who will be able to interact with other professional figures in diagnostics to monitor any problems [20] of this widespread practice [21].…”
Section: Discussionmentioning
confidence: 99%
“…To explore the opportunities, challenges, issues, and bottlenecks of integrating these tools (alone or interconnected) into the domain, this Special Issue [10] was initiated in May 2022, and was subsequently completed in January 2023. This Special Issue collected 17 contributions plus an editorial [1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and covered a wide range of topics, including:…”
mentioning
confidence: 99%
“…Pirrera et al [18] conducted an overview of Ats, using devices based on the control of the tongue with an arranged barbell piercing. They showed that these smart devices were promising, and suggested better integration into the health domain.…”
mentioning
confidence: 99%
See 2 more Smart Citations